Characterization of myeloid or lymphoid acute leukemia by a chemiluminescence assay: Comparison with immunocytochemistry using an antimyeloperoxidase antibody - Fonseca, Luiz Marcos da [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Rego, E. M. [UNESP]; Garcia, A. B. [UNESP]; Cilento, G. [UNESP]; Falcao, R. P. [UNESP] (Karger Publishers, 1993)
A simple and sensitive chemiluminescence assay for the demonstration of the activity of intracellular myeloperoxidase (MPO) is described, which is useful for the distinction between myeloid and lymphoid commitment in blasts from acute leukemia patients. When the cut-off point was settled at 13 mV of chemiluminescence all cases of acute myeloid leukemia (AML) were distinguished from those of acute lymphoid leukemia. In addition, this technique was able to demonstrate MPO activity in AML poorly differentiated (FAB-M0) which usually does not stain for MPO in classical cytochemistry preparations and could be negative also by immunocytochemistry with anti-MPO monoclonal antibody. Therefore the method here described presented a higher sensitivity than the immunocytochemistry procedure with anti-MPO.
Keywords: Acute leukemia; Antimyeloperoxidase; Chemiluminescence; Myeloperoxidase; myeloperoxidase; acute granulocytic leukemia; acute lymphocytic leukemia; adolescent; adult; aged; bone marrow biopsy; chemoluminescence; child; controlled study; diagnostic accuracy; enzyme activity; human; human tissue; immunocytochemistry; infant; intermethod comparison; major clinical study; priority journal; Acute Disease; Adolescent; Adult; Aged; Aged, 80 and over; Antibodies, Monoclonal; Child; Child, Preschool; Comparative Study; Diagnosis, Differential; Human; Immunohistochemistry; Immunophenotyping; Infant; Leukemia, Lymphocytic, Acute; Leukemia, Myeloid; Middle Age; Peroxidase; Sensitivity and Specificity; Support, Non-U.S. Gov't